SN 2016iyc: a Type IIb supernova arising from a low-mass progenitor. Issue 2 (22nd August 2022) - Aryan, Amar; Pandey, S B; Zheng, WeiKang; Filippenko, Alexei V; Vinko, Jozsef; Ouchi, Ryoma; Brink, Thomas G; Halle, Andrew; Molloy, Jeffrey; Kumar, Sahana; Halevi, Goni; Kilpatrick, Charles D; et al.
ABSTRACT: In this work, photometric and spectroscopic analyses of a very low-luminosity Type IIb supernova (SN) 2016iyc have been performed. SN 2016iyc lies near the faint end among the distribution of similar supernovae (SNe). Given lower ejecta mass ( M ej ) and low nickel mass ( M Ni ) from the literature, combined with SN 2016iyc lying near the faint end, one-dimensional stellar evolution models of 9–14 M⊙ zero-age main-sequence (ZAMS) stars as the possible progenitors of SN 2016iyc have been performed using the publicly available code mesa . Moreover, synthetic explosions of the progenitor models have been simulated, using the hydrodynamic evolution codes stella and snec . The bolometric luminosity light curve and photospheric velocities produced through synthetic explosions of ZAMS stars of mass in the range of 12–13 M⊙ having a pre-supernova radius R 0  = (204–300) R⊙, with M ej  = (1.89–1.93) M⊙, explosion energy E exp  = (0.28–0.35) × 10 51  erg, and M Ni < 0.09 M⊙, are in good agreement with observations; thus, SN 2016iyc probably exploded from a progenitor near the lower mass limits for SNe IIb. Finally, hydrodynamic simulations of the explosions of SN 2016gkg and SN 2011fu have also been performed to compare intermediate- and high-luminosity examples among well-studied SNe IIb. The results of progenitor modelling and synthetic explosions for SN 2016iyc, SN 2016gkg, and SN 2011fu exhibit a diverse range of mass for the possible progenitors of SNe IIb.